A estética literária na poesia de mulheres surdas nordestinas - Ramalho, Hosana Gouveia (2024)
This dissertation aims to explore the aesthetic elements present in the literature developed by deaf women from the Northeast region. Through a qualitative and exploratory approach, we analyze selected literary works from these women in literary events in the Northeast, focusing on the aesthetic elements proposed by Sutton-Spence (2021). Our study delves into literary elements, the use of sign language, and the influence of deaf culture on their artistic expressions. The research is qualitative and exploratory, with Sutton-Spence (2021) as the theoretical and methodological framework concerning literary productions within deaf cultures. The corpus consists of three poems created by artists from Paraíba, presented in online literary events on the YouTube platform, in reference to Northeastern Day. The works respectively address the resistance of the Northeastern people; the routine of sertanejos amid the COVID-19 pandemic; and the character Maria Bonita. In the analyses, we identify the predominant presence of visual and imagistic elements, including classifiers, personifications, non-manual elements, metaphors, aesthetic spatial structures, multiple perspectives, repetition, rhythm, and rhyme. This investigation not only expands our understanding of the literary aesthetics of deaf Northeastern poets but also underscores the importance of recognizing and valuing the confluence of deaf and Northeastern culture. Consequently, by disseminating these findings, we hope to promote greater visibility and appreciation of deaf cultures in the Northeastern context, especially those of women.